Answer:
y = -0.07x2 + 3.07x
Step-by-step explanation:
For each plant we add, there is a decrease of 70 grams for all plants from the inicial value of 3 kg of beans.
So, for 2 plants, we have (3 - 0.07) * 2
For 3 plants, we have (3 - 2*0.07) * 3
For x plants, we have (3 - (x-1)*0.07) * x
So we can model the final result of the amount of beans 'y' with the equation:
y = (3 - (x-1)*0.07) * x
y = (3 - 0.07x + 0.07) * x
y = (3.07 - 0.07x) * x
y = -0.07x2 + 3.07x
(In this equation we have a = -0.07, b = 3.07 and c = 0)
the correct option is answer choice D, because there are multiple 2's in the x column with different f(x) values.
Answer:-111
Step-by-step explanation:
Answer:
-4< c
Step-by-step explanation:
2> -2-c
Add 2 to each side
2+2> -2+2-c.
4 > -c
Divide each side by -1. Remember that dividing by -1 will flip the inequality.
4/-1 < -c/-1
-4< c
Answer:
(3x + 1)²
Step-by-step explanation:
Given
9x² + 6x + 1 ← is a perfect square of the form
(ax + b)² = a²x² + 2abx + b²
Compare like terms to find a and b
a²x² = 9x² ⇒ a² = 9 ⇒ a = = 3
b² = 1 ⇒ b = = 1
and 2ab = 2 × 3 × 1 = 6
Thus
9x² + 6x + 1 = (3x + 1)²